The Origins of the Studium of Medicine of Bologna: a Status Quaestionis - Duranti, Tommaso (CIAN-Revista de Historia de las Universidades, 2018)
This article deals with the birth of the Studium of Medicine in Bologna during the 13th century. The theme of the beginning of teaching in a context of spontaneous origin highlights the fluidity of the object of the research. Also through a comparative analysis; it is possible to follow the growing interest in teaching medicine before the birth of the universitas as an associative institution. In fact; some clues show the progressive stabilization of these teachings: their institutional consecration corresponded to the end of a process of affirmation and to the definitive recognition for students and teachers of medical and artistic disciplines as autonomous organizations.